2020
DOI: 10.1097/sla.0000000000004072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Retrocolic Versus Antecolic Route for Alimentary Tract Reconstruction on Delayed Gastric Emptying After Pancreatoduodenectomy

Abstract: Objective:This study aimed to determine whether retrocolic alimentary tract reconstruction is noninferior to antecolic reconstruction in terms of DGE incidence after pancreatoduodenectomy (PD) and investigated patients’ postoperative nutritional status.Summary of Background Data:The influence of the route of alimentary tract reconstruction on DGE after PD is controversial.Methods:Patients from 9 participating institutions scheduled for PD were randomly allocated to the retrocolic or antecolic reconstruction gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…Ages, gender mix and BMI were generally comparable between direct comparisons, although the single study comparing PR, retrocolic, Billroth II against PR, antecolic Billroth II had a male-predominant cohort (more than 70 per cent). Most studies were conducted in Asia (16 of 24; 67 per cent) 5 , 35 , 36 , 38–46 , 48 , 50 , 51 , 53 , 10 of which were in Japan 5 , 35 , 36 , 39 , 42 , 44 , 46 , 48 , 50 , 51 . Study characteristics are summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ages, gender mix and BMI were generally comparable between direct comparisons, although the single study comparing PR, retrocolic, Billroth II against PR, antecolic Billroth II had a male-predominant cohort (more than 70 per cent). Most studies were conducted in Asia (16 of 24; 67 per cent) 5 , 35 , 36 , 38–46 , 48 , 50 , 51 , 53 , 10 of which were in Japan 5 , 35 , 36 , 39 , 42 , 44 , 46 , 48 , 50 , 51 . Study characteristics are summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 15 studies used the ISGPF definition for POPF. Only five studies reported the rates of prokinetic use after PD 25,38 . Only three studies reported rates of parenteral nutrition (30-45%), with no differences between comparator arms 3,39,40 .…”
Section: Resultsmentioning
confidence: 99%
“…Ages, gender mix and BMI were generally comparable between direct comparisons, however, the single study comparing PR, retrocolic, Billroth II against PR, antecolic Billroth II had a male predominant cohort (>70%). Most studies were conducted in Asia (16/24; 67%) 38,39,4154 , 10 of which were in Japan 4143,46,47,4953 . Study characteristics are summarised in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations